2022
DOI: 10.17161/kjm.vol15.16522
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Metabolic-associated Fatty Liver Disease with Clinical Outcomes of COVID-19: A Systematic Review and Meta-Analysis

Abstract: Introduction. Metabolic-associated fatty liver disease (MAFLD) is a hepatic manifestation of metabolic syndrome (MS). MAFLD patients have a higher prevalence of COVID-19. MAFLD is also associated with worse clinical outcomes of COVID-19, such as disease severity, ICU admission rate, and higher mortality rates. However, this evidence has not been well characterized in the literature. This meta-analysis aims to determine the clinical outcomes of COVID-19 among MAFLD patients compared to the non-MAFLD group.  Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…In the first meta-analysis of 4 studies [68-71] Pan et al [72] reported a pooled prevalence of 0.31 (95% CI: 0.28-0.35) of NAFLD among COVID-19 patients. Similarly, Hayat et al [73] in a meta-analysis of 16 studies found a pooled prevalence of COVID-19 among NAFLD patients of 0.29 (95% CI: 0.19-0.40; p < 0.001).…”
Section: Prevalence Of Nafld In Covid-19 Patientsmentioning
confidence: 82%
See 1 more Smart Citation
“…In the first meta-analysis of 4 studies [68-71] Pan et al [72] reported a pooled prevalence of 0.31 (95% CI: 0.28-0.35) of NAFLD among COVID-19 patients. Similarly, Hayat et al [73] in a meta-analysis of 16 studies found a pooled prevalence of COVID-19 among NAFLD patients of 0.29 (95% CI: 0.19-0.40; p < 0.001).…”
Section: Prevalence Of Nafld In Covid-19 Patientsmentioning
confidence: 82%
“…Although some studies have reported that negative outcomes are similar in COVID-19 patients with and without NAFLD, a systematic review specifically assessed NAFLD as a risk factor in patients with COVID-19 and revealed pooled OR for severe COVID-19 in NAFLD [82] while tree systematic reviews with meta-analysis looked several studies to conclude that NAFLD was associated with increased risk of severe COVID-19 and ICU admission [73][74][75][76][77][78][79][80][81][82][83][84] In summary, many studies highlight the role of NAFLD in the progression of COVID-19, but there is still no evidence that NAFLD will affect the prognosis of COVID-19 [85].…”
Section: Covid-19 Severity In Patients With Nafldmentioning
confidence: 99%
“…Meta-analysis of observational studies suggests that metabolic dysfunction associated fatty liver disease (MAFLD) independent risk factor for developing severe COVID-19, requiring hospitalization and ICU admission, but not for mortality [19] . Among obese adults, those with MALFD were 6 times more likely to develop severe COVID-19 compared to those without MAFLD [20] .…”
Section: Metabolic Syndrome As a Risk Factor For Adverse Covid-19 Out...mentioning
confidence: 99%
“…Over the past two decades, the prevalence of CLD has been increasing[ 11 ]. CLD includes NAFLD, alcohol-related liver disease (ALD), and chronic viral hepatitis B and C[ 12 ], and it can progress to fibrosis, cirrhosis, and HCC[ 13 ]. NAFLD, or the recently defined metabolic-associated fatty liver disease (MAFLD), are the most common CLDs, which affect about a quarter of the world’s adult population[ 14 ].…”
Section: Global Burden Of Liver Diseasesmentioning
confidence: 99%
“…A systematic review and meta-analysis showed that the proportion of patients with MAFLD and NAFLD ranged from 28% to 50% and from 6% to 38%, respectively, and found that the presence of MAFLD and NAFLD was associated with worse clinical outcomes for COVID - 19[ 67 ]. Although several studies also showed significant associations between MAFLD and NAFLD and severe COVID-19 outcomes[ 13 , 68 ], there is still no strong evidence that the presence of MAFLD affects its prognosis[ 65 ].…”
Section: Covid-19 In Patients With Pre-existing Liver Diseasementioning
confidence: 99%